La vita di Cola di Rienzo - D'Annunzio, Gabriele, 1863-1938 (Salt Lake City, UT : Project Gutenberg, 2021)
"La vita di Cola di Rienzo" by Gabriele D'Annunzio is a historical account written in the early 20th century. This work delves into the life of Cola di Rienzo, a notable figure from the medieval period known for his attempt to revive the power of the Roman Senate and restore Rome to its former grandeur. Through a rich narrative that intertwines personal traits with historical context, D'Annunzio presents a complex character in Rienzo, offering readers an immersive glimpse into the ambitions and struggles of the era. The opening of the text sets the tone with a prologue by the author, reflecting on the nature of biography and the distinction between historical figures celebrated for their deeds and lesser-known individuals who similarly shaped the fabric of society. D'Annunzio draws comparisons between noteworthy personalities and the personal anecdotes that highlight the essence of character in biographical writing. With vivid descriptions and introspective commentary, he expresses the challenges and privileges involved in portraying historical complexities$1 (Bcapturing both the grandeur of public life and the unique traits of individuals like Cola di Rienzo, who sought transformation amid the turbulence of their times. (This is an automatically generated summary.)s
Release date is 2021-04-13
Barbara Magni and the Online Distributed Proofreading Team at http://www.pgdp.net (This file was produced from images made available by The Internet Archive)
Keywords: Historical fiction; Rienzo, Cola di, -1354 -- Fiction; Rome (Italy) -- History -- 476-1420 -- Fiction; Revolutionaries -- Italy -- Rome -- Fiction